Growth performance and total tract digestibility of nutrients for weanling pigs are improved by an exogenous xylanase and a stimbiotic regardless of maternal xylanase consumption - Jessica P. Acosta; Charmaine D. Espinosa; Gemma González-Ortiz; Hans H. Stein (Journal of Animal Science and Biotechnology)
Abstract Background Exogenous xylanase can increase utilization of fiber and energy when included in diets for pigs, and xylo-oligosaccharides (XOS) may improve growth performance of pigs by modulating intestinal fermentation. However, it is unclear if a stimbiotic (i.e., a combination of xylanase and XOS) has superior effects compared with a xylanase alone, and there is a lack of data demonstrating if xylanase fed to lactating sows influences growth performance of weanling pigs. Therefore, two hypotheses were tested: 1) xylanase and stimbiotic improve growth performance, apparent total tract digestibility (ATTD) of gross energy (GE) and total dietary fiber (TDF), digestible energy (DE), and intestinal health of weanling pigs and 2) offspring of sows fed xylanase in lactation have greater growth performance after weaning than offspring of sows fed no xylanase during lactation. Methods One hundred and twenty pigs were weaned from sows fed a diet without xylanase, and 120 pigs were weaned from sows fed a lactation diet containing 16,000 beechwood xylanase units per kg (initial weight: 5.81 ± 0.50 kg). Pigs were allotted to a 2 × 3 factorial with two sow groups (lactation diet without or with xylanase) and three dietary treatments (i.e., control, control plus xylanase, or control plus stimbiotic). Results There were no interactions between sow treatment and post-weaning pig treatment, and sow treatment did not impact post-weaning growth or ATTD of GE and TDF in weaned pigs. From d 15 to 28 post-weaning, the ADG, G:F, ATTD of GE and TDF, and concentration of DE were greater (P < 0.05) for pigs fed the diet with stimbiotic than if fed the xylanase diet or the control diet, and pigs fed the xylanase diet had greater (P < 0.05) ADG, G:F, ATTD of GE and TDF, and concentration of DE than pigs fed the control diet. From d 29 to 42 post-weaning, pigs fed the diets with xylanase or stimbiotic had greater (P < 0.05) ADG, ATTD of GE and TDF, and DE than pigs fed the control diet. Conclusions Pigs fed xylanase or stimbiotic had greater ATTD of GE and TDF, greater DE, and greater overall ADG, G:F, and final body weight on d 42 post-weaning than pigs fed the control diet, but feeding sows xylanase in lactation did not influence post-weaning growth performance.